2007
DOI: 10.1111/j.1365-2486.2007.01477.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic differences in leaf biochemical, physiological and growth responses to ozone in 20 winter wheat cultivars released over the past 60 years

Abstract: Ozone (O 3 ) concentrations in periurban areas in East Asia are sufficiently high to decrease crop yield. However, little is known about the genotypic differences in O 3 sensitivity in winter wheat in relation to year of cultivar release. This paper reports genotypic variations in O 3 sensitivity in 20 winter wheat cultivars released over the past 60 years in China highlighting O 3 -induced mechanisms. Wheat plants were exposed to elevated O 3 (82 ppb O 3 , 7 h day À1 ) or charcoal-filtered air (o5 ppb O 3 ) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(123 citation statements)
references
References 53 publications
8
113
1
1
Order By: Relevance
“…Numerous studies have shown that elevated [O 3 ] generally results in reduced photosynthesis and whole-plant growth, decreased stomatal conductance, altered antioxidant system, and accelerated senescence, although the extent of the effects varies by species or even cultivars (Ainsworth, 2008;Ashmore, 2005;Biswas et al, 2008;Clarke et al, 1990;Feng et al, 2006Feng et al, , 2008; Long and Naidu, 2002;Morgan et al, 2003Morgan et al, , 2006. Furthermore, elevated [O 3 ] can increase respiration rates and affect carbon allocation patterns, resulting in a decreased root: shoot ratio (Andersen, 2003;Biswas et al, 2008;Feng et al, 2006;Nouchi et al, 1995), or decreases in the leaf area ratio and specific leaf area (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that elevated [O 3 ] generally results in reduced photosynthesis and whole-plant growth, decreased stomatal conductance, altered antioxidant system, and accelerated senescence, although the extent of the effects varies by species or even cultivars (Ainsworth, 2008;Ashmore, 2005;Biswas et al, 2008;Clarke et al, 1990;Feng et al, 2006Feng et al, , 2008; Long and Naidu, 2002;Morgan et al, 2003Morgan et al, , 2006. Furthermore, elevated [O 3 ] can increase respiration rates and affect carbon allocation patterns, resulting in a decreased root: shoot ratio (Andersen, 2003;Biswas et al, 2008;Feng et al, 2006;Nouchi et al, 1995), or decreases in the leaf area ratio and specific leaf area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, elevated [O 3 ] can increase respiration rates and affect carbon allocation patterns, resulting in a decreased root: shoot ratio (Andersen, 2003;Biswas et al, 2008;Feng et al, 2006;Nouchi et al, 1995), or decreases in the leaf area ratio and specific leaf area (e.g. Morgan et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of plants to O 3 has been linked to O 3 flux controlled by stomata (Dizengremel et al, 2009;Fiscus et al, 2005) and antioxidant capacity determined by antioxidant pools and enzymes (Biswas et al, 2008;Feng et al, 2010;Inada et al, 2012;Li et al, 2016;Wang et al, 2014aWang et al, , 2014b. However, there was no significant interaction between cultivar and O 3 in g s across the four measurements (Table 1, a a a a a a Fig.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that modern wheat cultivars are more sensitive to O 3 than old accessions due to higher g s and lower levels of antioxidant capacity (Pleijel et al, 2006), and that they are subjected to larger oxidative damages to proteins and cellular membranes (Biswas et al, 2008). In this study, five modern cultivars showed variable reduction of A sat at mid-grain filling stage with a wide range from 16% to78% when exposed to an elevation of average 8 h- [O 3 ] (9:00-17:00) from 44.4 ppb to 56.4 ppb , which suggests the presence of intraspecific variation in the response to elevated [O 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation